RiceAdvice Voucher System: a new business approach to test the scaling of RiceAdvice with farmers paying service providers in Nigeria - CGIAR Research Program on Rice (2019)
Implementation of the voucher system business model started in 2019 in Lafia (Nasarawa State/ Nigeria). The initial phase involved 500 farmers, 5 service providers and 5 input dealer shops.